Answer :
Answer:
(-2,2)
Step-by-step explanation:
the value of "y" is already given so lets substitute that in the second equation:
x+4=-2x-2
2) bring all like terms to one side
x+2x=-4-2
3x=-6
x=-2
substitute "-2" as "x" in the first equation:
y=(-2)+4
y=2
Hope this helps!
Answer:
(-2, 2).
Step-by-step explanation:
y = x + 4
y = -2x - 2
Substitute y = x + 4 in the second equation:
x + 4 = -2x - 2
x + 2x = -2 - 4
3x = -6
x = -2.
To get the value of y we substitute x = -2 in the first equation:
y = -2 + 4
y = 2.
Check the result by substituting for x and y in the second equation:
y = -2x - 2
2 = -2(-2) - 2
= 4 - 2 = 2.
- checked.